A new species of the genus Tridactylophagus Subramaniam, 1932 from West Bengal, India with a tentative phylogeny and world key to known males (Strepsiptera: Halictophagidae) - Hui, Poulami; Mukherjee, Bindarika; Hazra, Niladri (Zootaxa, 2023)
A new species of the genus Tridactylophagus Subramaniam is described and illustrated from West Bengal, India. The new species, T. sufflatus differs from other members of Tridactylophagus by having a flattened, fist-shaped first tarsomere in forelegs and a slightly bulged out antennomere IV on the distal end with a sensory spot on one side. Molecular barcoding of the new species is done. Cladistic analysis and a revised world key of the males of the genus Tridactylophagus are also provided.